Immobilizing Alcalase® Enzyme onto Magnetic Nanoparticles - Huu, Cao Xuan; Linh, Nguyen Bao; Yen, Nguyen Thi Hoang; Long, Dang Duc (Communications in Physics, 2014)
<!--[if gte mso 9]> <![endif]--> In recent years, magnetic nanoparticles (MNPs) have been applied to numerous biological systems. The nanoparticles are particularly useful in separating biological molecules due to its low price, scalable ability and very little interference. Here, MNPs, which can efficiently separate biocatalysts from reaction media by external magnet, was used to immobilize an alkaline protease (Alcalase®). Covalent attachment of the enzyme to MNPs began with the functionalization of the MNPs' surface with amines (APTES). Then, glutaraldehyde was introduced to link the MNP surface amines with enzyme surface amine residues, typically lysine. Successful covalent bonds were checked by FT-IR. Our results showed the attached enzyme did not affect superparamagnetic property of MNPs, therefore the MNPs-attached enzyme was easily recovered after the reaction. The immobilized enzyme maintained its activities after 10 times of recycle uses. <!--[if gte mso 9]> Normal 0 false false false VI X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->